(untitled) (Progress Annals: Journal of Progressive Research, 2023)
The school buildings are critical pieces of infrastructure in every country. Several aspects, including structural safety, utility, and economic feasibility, must be carefully considered while creating these structures. The goal of this study is to look at the available research on the structural analysis and design of primary school buildings, particularly four-story structures, in Savar Upazila, Dhaka